2015
DOI: 10.1016/j.atherosclerosis.2015.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Biologic plausibility, cellular effects, and molecular mechanisms of eicosapentaenoic acid (EPA) in atherosclerosis

Abstract: Residual cardiovascular (CV) risk remains in dyslipidemic patients despite intensive statin therapy, underscoring the need for additional intervention. Eicosapentaenoic acid (EPA), an omega-3 polyunsaturated fatty acid, is incorporated into membrane phospholipids and atherosclerotic plaques and exerts beneficial effects on the pathophysiologic cascade from onset of plaque formation through rupture. Specific salutary actions have been reported relating to endothelial function, oxidative stress, foam cell format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 155 publications
(125 citation statements)
references
References 108 publications
2
121
1
1
Order By: Relevance
“…In addition, EPA exerted beneficial effects on the pathophysiologic cascade from onset of plaque formation to rupture by incorporating into membrane phospholipids and atherosclerotic plaques. EPA also improved atherogenic dyslipidemia characterized by reduction of triglycerides without raising low-density lipoprotein cholesterol [50]. Based on the result of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EPA exerted beneficial effects on the pathophysiologic cascade from onset of plaque formation to rupture by incorporating into membrane phospholipids and atherosclerotic plaques. EPA also improved atherogenic dyslipidemia characterized by reduction of triglycerides without raising low-density lipoprotein cholesterol [50]. Based on the result of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…EPA has favorable effects on various atherogenic parameters including reductions in the plasma levels of triglycerides (TGs), non-high-density lipoprotein cholesterol (non-HDL-C), apolipoprotein B (apoB), remnant-like particle cholesterol (RLP-C), apolipoprotein C-III (apoC-III), and oxidized low-density lipoprotein (ox-LDL) particles [4,5]. Importantly, EPA does not increase LDL-C levels [5].…”
Section: Effects Of Epa On Lipids and Lipoproteinsmentioning
confidence: 99%
“…The evidence supporting beneficial effects of EPA on multiple steps of the atherosclerotic pathway has been reviewed extensively [4,14]. Figure 2 provides an overview of the pleiotropic effects of EPA in the atherosclerotic pathway [15].…”
Section: Pleiotropic Effects Of Epa In the Atherosclerotic Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent meta-analysis suggested that beneficial effects of statin therapy in patients with renal dysfunction are significantly related to the level of residual kidney function [16]. Of particular interest was the observation that there was no clear relationship between LDL-C reduction and CV benefit in patients on hemodialysis [16,17]. …”
Section: Unmet Needs With Traditional Approaches To Mitigation Of Carmentioning
confidence: 99%